INTELLIGENT TRAINING PROCESS MANAGEMENT - POLIBINA, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article discusses the development of an intelligent training system (ITS), types of technologies in ITS and their use in intelligent management of the learning process. The article gives the examples of models and describes an overlay fuzzy model of a student’s knowledge based on the concept of a didactic unit. The research methods include a systematic approach to the development of the ITS concept and knowledge processing models based on the use of adaptive testing theories, fuzzy logic, artificial intelligence. The proposed concept of building an ITS using an overlay fuzzy model of the student’s knowledge will determine the degree of mastering the didactic units and competencies of the student. The results obtained are of interest in building an intelligent training systems and training complexes, which, in turn, help to increase the efficiency of training due to the openness, multifunctionality and adaptability of intelligent training systems. In connection with the growing interest in the design of intelligent training systems, there are many ambiguities in the interpretation of the types of learner models in ITS. However, since new directions in the modeling of ITS for trainees have appeared, innovative technologies of the learning process itself have been developed. This article is relevant in this regard, especially if we consider the application of theoretical ideas into practice and use of ITS in the intelligent management of education. This article discusses the concept of building an ITS in the Nova KakhovkaInstrument Making Applied College. The one of the tasks of ITS should be dynamic adaptation of educational material to the level of student knowledge. The training model proposed in the article allows: to adjust the learning goals set by teachers to the goals of students, to increase the independence of learning, responsibility and conscientiousness of students, to increase the share and quality of independent learning, to ensure the unity of training and educational processes.